1991
DOI: 10.1038/bjc.1991.304
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in patients with advanced cancer of the breast: prevalence measured by two self-rating questionnaires

Abstract: Summary Two hundred and twenty-two women with advanced cancer of the breast were asked to complete two previously validated self-assessment questionnaires (Hospital Anxiety and Depression Scale (HADS) There has been extensive investigation into the psychological sequelae of early breast cancer and its treatment (Maguire et al., 1978;Maguire et al., 1980;Morris et al., 1977;Robert et al., 1972) but there are few data concerning the prevalence of depression and anxiety in patients with advanced disease. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
88
1
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(103 citation statements)
references
References 16 publications
12
88
1
2
Order By: Relevance
“…For 'borderline cases' the percentages for anxiety were 22% and 9% for patients with post-treatment and anticipatory symptoms respectively, and for depression were 18% and 27%. Combining the number of borderline and clear cases for both groups experiencing some nausea and emesis the percentages in the group as a whole for anxiety (20%) are similar, and for depression (22%) higher, than levels reported elsewhere in a survey of recently diagnosed patients taken from the same hospital (Greer et al, 1992), but both are slightly lower than the numbers observed in breast cancer patients with advanced disease (Hopwood et al, 1991). However, it is clear that patients without the nausea and emesis side-effects experience an extremely low level of psychological morbidity.…”
Section: Resultsmentioning
confidence: 59%
“…For 'borderline cases' the percentages for anxiety were 22% and 9% for patients with post-treatment and anticipatory symptoms respectively, and for depression were 18% and 27%. Combining the number of borderline and clear cases for both groups experiencing some nausea and emesis the percentages in the group as a whole for anxiety (20%) are similar, and for depression (22%) higher, than levels reported elsewhere in a survey of recently diagnosed patients taken from the same hospital (Greer et al, 1992), but both are slightly lower than the numbers observed in breast cancer patients with advanced disease (Hopwood et al, 1991). However, it is clear that patients without the nausea and emesis side-effects experience an extremely low level of psychological morbidity.…”
Section: Resultsmentioning
confidence: 59%
“…The fact that the same pattern was not found in the CT group where the side-effects from treatment were less intensive, that the discrepancies in mean depression scores were so great when the 'fatigue' item was taken out from the analyses, and the significant correlation between depression and the Karnofsky scores when the patients scored lowest regarding performance status, lends support to this. The relationship between the depression scale of the HADS and physical symptoms has been mentioned by other, 15,17 and warrants further investigation. Thus, the higher levels of psychiatric distress reported from other studies might be explained by the use of questionnaires such as the BDI, which includes more somatic symptoms than the HADS.…”
Section: Discussionmentioning
confidence: 99%
“…All ASCT patients had received combination chemotherapy according to standard treatment protocols prior to transplant, compared with 30 SCT patients (49%), those suffering from AML or ALL. Thirty SCT patients with CML had received hydroxyurea; as monotherapy (17), or in combination with interferon ␣2b (11), or busulphan (two), while one patient had received no treatment. One SCT patient (2%) had received additional radiotherapy to the central nervous system as part of primary treatment, compared with 19 (28%) of the ASCT patients (P Ͻ 0.0001).…”
Section: Sct and Asct Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies only include patients with early stages of breast cancer [35,36], while others have investigated more advanced breast cancer [11,23,37]. Stage of disease and tumor grade have been reported inconsistently related to psychological problems in cancer and is generally uncorrelated with depression in breastcancer [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%